Kesinambungan dan Perbedaan Rumah Sumba di Dalam dan di Luar Praingu - Yohanes Djarot Purbadi; B. Sumardiyanto; Vincentia Reni Vitasurya (CV. Gio Architect, 2023)
The Sumba house is characterized by traditional architecture on the island of Sumba, some of which have changed from their original characteristics and some others have retained their original characteristics. If you compare the Sumba houses in praingu (traditional villages) with the houses of Sumbanese people in cities or along roads that are characterized by modern or contemporary houses, the differences in characteristics are easy to see. It is different if the houses with Sumba architectural characteristics outside Praingu are compared to those inside Praingu. There are interesting things to say. They look the same, but have significant differences. This paper aims to describe the continuity and different of Sumba houses with traditional Sumba architecture in Anakalang compared to the original Sumba houses located in Praingu Galubakul. The focus of this research is to look at the continuity and differences in the form-function-meaning aspects of traditional Sumba houses within praingu and outside praingu. This research was produced through a qualitative research process based on a phenomenological-husserlian approach, using field observation and in-depth interview methods. The case is the Sumba house in Anakalang which is outside Praingu (Galubakul) and the owner is bound by Sumba culture. There is continuity and different in the Sumba house in Anakalang. Form and meaning continue to be continuous, but there is a change in the function of the building. Continuity occurs due to aspects of adherence to tradition, while changes occur in the addition of new functions, changing functions and deleting functions due to the establishment of a modern lifestyle. The religious (spiritual) aspect of the homeowners related to the Marapu belief and fear of praingu integration is a determining factor for the continuity of the form and meaning of the architecture of the Sumba house. Modern lifestyle is a determining factor in changing the center room from the status of a sacred space to a profane space.